2022
DOI: 10.35975/apic.v26i6.2055
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between bupivacaine 0.5% vs. bupivacaine 0.5% plus lidocaine 2% vs. lidocaine 1.5% in ultrasound guided axillary brachial plexus block for brachiocephalic fistula formation in chronic renal failure patients

Abstract: Abstract Background: Patients with chronic renal insufficiency need to have arteriovenous fistula (AVF) for hemodialysis.Ultrasound guided axillary brachial plexus block is a good substitute to general anesthesia or local anesthesia as it causes vasodilatation and minimum hemodynamic derangement, besides offering prolonged postoperative analgesia. We compared three types of local anesthetic solutions; bupivacaine 0.5%, bupivacaine 0.5% plus lidocaine2% and lidocaine 1.5% for onset and duration when used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Abdelhady et al compared bupivacaine alone with bupivacaine plus lidocaine for axillary brachial plexus block, and the results showed that regarding the onset of sensory anesthesia, there was a statistically non-significant difference between both groups where the combination group had a shorter time of onset than bupivacaine alone group,i.e., 9.05±1.36 versus 9.77±0.97 minutes. (Abdelhady et al, 2022) A study determined the difference in duration of effect by adding 0.5% bupivacaine to 2% lidocaine compared to 2% lidocaine with adrenaline. It was revealed that the block duration was longer in the combination group compared to the group where lidocaine was used alone, i.e., 5.7 hours versus 3.9 hours (Chongarunngamsang, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Abdelhady et al compared bupivacaine alone with bupivacaine plus lidocaine for axillary brachial plexus block, and the results showed that regarding the onset of sensory anesthesia, there was a statistically non-significant difference between both groups where the combination group had a shorter time of onset than bupivacaine alone group,i.e., 9.05±1.36 versus 9.77±0.97 minutes. (Abdelhady et al, 2022) A study determined the difference in duration of effect by adding 0.5% bupivacaine to 2% lidocaine compared to 2% lidocaine with adrenaline. It was revealed that the block duration was longer in the combination group compared to the group where lidocaine was used alone, i.e., 5.7 hours versus 3.9 hours (Chongarunngamsang, 2017).…”
Section: Discussionmentioning
confidence: 99%